2002
DOI: 10.1007/s00520-002-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of complimentary and alternative medicine by breast cancer patients: prevalence, patterns and communication with physicians

Abstract: This study examined the use of complementary and alternative medicine (CAM) therapies by breast cancer patients and the communication of their CAM use to their physicians relative to lymphedema symptoms and other factors. Breast cancer patients ( N = 148) in the State of Vermont were interviewed 2-3 years after their primary surgery using computer-aided telephone interviewing methods. Questionnaire items included demographic information, treatment, CAM use, lymphedema symptoms, and other measures. A large prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
5
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 15 publications
7
113
5
2
Order By: Relevance
“…This is comparable to the 32.7% reported in an earlier study of Korean cancer patients and 29.6% in Malaysian patients with cancer [32,34]. However, it is much lower than the 71% reported by breast cancer patients in USA [36]. A systematic review of the characteristics of CAM use among breast cancer patients indicated that more than half of patients do not disclose CAM use to their doctors [37].…”
Section: Discussionsupporting
confidence: 58%
“…This is comparable to the 32.7% reported in an earlier study of Korean cancer patients and 29.6% in Malaysian patients with cancer [32,34]. However, it is much lower than the 71% reported by breast cancer patients in USA [36]. A systematic review of the characteristics of CAM use among breast cancer patients indicated that more than half of patients do not disclose CAM use to their doctors [37].…”
Section: Discussionsupporting
confidence: 58%
“…Six of these, published in 1999 to 2001, [14][15][16][17][18][19] are summarized in an article by Lengacher et al 20 An additional review of 13 studies published from 2002 to 2006 is summarized in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33] Upon review, certain patterns, associations, and predictors of CAM use emerge as commonalities for women with breast cancer. In all of the studies that examined demographic associations with CAM use, women were younger 14,21 and had more education.…”
Section: Complementary and Alternative Medicine Use For Breast Cancermentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] Upon review, certain patterns, associations, and predictors of CAM use emerge as commonalities for women with breast cancer. In all of the studies that examined demographic associations with CAM use, women were younger 14,21 and had more education. 33 When demographic predictors of CAM use were studied, it was consistently found that women were younger, 7,22,26,27 more educated, 17,22,26,27,29,31,33 and insured.…”
Section: Complementary and Alternative Medicine Use For Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have reported an even higher prevalence of between 70 and 80% (Richardson et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002). The nature of CAMs used, for example, vitamins and other supplements, herbal remedies, physical and psychological treatments, also varies greatly (Risberg et al, 1998;Richardson et al, 2000;Sparber et al, 2000;Bernstein and Grasso, 2001;Ashikaga et al, 2002).…”
mentioning
confidence: 99%